Speciality Rice Varieties and Landraces - Karkee, S. S. (Journal of Agriculture and Environment, 2021)
Rice is a staple food for half of the world's population and is the major source of calories for the people of rice-growing countries. Nowadays, nutritionists are more concerned about hidden hunger as people with sufficient food intake may be deprived of important nutrients that may be absent in the food they consume. Similarly, white rice (polished rice) that only contains endosperm is lacking several essential nutrients like Fe, Zn, fiber, and antioxidant compounds, etc. To increase the nutritive content of these rice and minimize the problem of hidden hunger, different rice varieties are being tested with artificial addition of nutrients, such varieties are called biofortified rice. Special rice like black, purple, brown rice, contain natural antioxidant compounds in their outer bran layer, aromatic rice is rice in aroma, glutinous rice is popular for their sticky and sweet test. At the same time these special rice are also rich in several micronutrients. In addition to nutrition content, people's taste preferences are also considered a major concern. This review paper focused on specialty rice varieties and landraces along with their unique values.